PENGARUH PROGRAM TELEVISI DETAK KEPRI DAN OPINI PUBLIK TERHADAP SIKAP PEMILIH DI KOTA BATAM - partahi nando sirait (Prodi Ilmu Komunikasi Universitas Putera Batam, 2018)
Technology in the development of the flow of production, consumption and distribution of information becomes vital. The urgency of the role of technology in information masification is also used by mass media, especially electronic mass media such as television. The development of electronic mass media to date, is also increasingly promising for all parties, not apart from the political elite who use or cooperate with the mass media crew in presenting various programs. Not only that, the news program was no less interesting to most political actors in order to generate opinions among the people themselves. As in the presidential election some time ago, the role of mass media and its news program succeeded in changing people's attitudes towards the figure of a presidential candidate. The problems and use of electronic mass media are considered to be enough to attract sympathy from the public, where in the news program on television the public can see and hear directly what is done and spoken by the political elite. And this can also give rise to responses to opinions in the community.